The value of molecular markers in classification and prediction of progression in non-muscle-invasive bladder cancer - Pan, Chin-Chen (Translational Andrology and Urology, 2018)
Urothelial carcinoma is the most common type of bladder cancer. The majority of urothelial carcinomas are low-grade, papillary, non-muscle invasive bladder cancer (NMIBC) treated by transurethral resection followed by intravesical instillation (1). The remaining carcinomas consist of high-grade, muscle-invasive tumors that are eligible for cystectomy. A significant proportion of NMIBC recur following TUR, and a minority will progress into high-grade tumors that are either muscle-invasive or metastatic tumor (2). For NMIBC treated by TUR, diligent follow-up plans are paramount to detect recurrence and progression.